Layanan Pengecekan Judul Buku Menggunakan Algoritma Boyer-Moore pada Perpustakaan SDN Sumur Batu 4 Bantargebang Bekasi - Isnawati; Dwipa Handayani; Achmad Noeman (Journal of Informatic and Information Security, 2022)
in the library is one part of the processing and utilization of information at SDN Sumur Batu 4 Bantargebang Bekasi is still not computerized, manual searches or searches cause students to have difficulties in searching books and librarian can notcontrol books efficiently from school problems. a system that can solve problems so as to produce the goal of increasing efficiency in book searches, building a book title checking service system using the Boyer-Moore algorithm and providing convenience for all users in utilizing book searches. By implementing the book title checking service using the Boyer-Moore algorithm as the most efficient algorithm and using the rapid application development method starting from planning, design workshops, rapid application development and implementation. The data collection methods are observation, interviews, questionnaires and library studies. It is expected to be able to help speed up the process of searching for books in the library and to increase the satisfaction of library services for library visitors.